A POP CULTURE IN EDUCATION: AMUSING WAY TO ENHANCE STUDENTS' LISTENING SKILL - Dina Isramira Rizka; Farizi Rianto; Indriani (Juliet, 2023)
Listening is one of the four skills that educators must teach in language learning. Students appeared to struggle with listening, based on observations in the classroom. One of the pedagogical techniques for improving listening skills is pop culture. The goal of this study is to see how utilizing pop culture as a formative assessment for English language training might help students develop their listening skills in an enjoyable way. Because it is connected to students' lives and experiences, pop culture serves as a stimulus for eliciting ideas, knowledge, inspiration, and interest in listening comprehension.